Proceedings of the Forty-Fourth Annual ACM Symposium on Theory of Computing 2012
DOI: 10.1145/2213977.2214035
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of depth-4 multilinear circuits with top fan-in 2

Abstract: We present a randomized algorithm for reconstructing multilinear ΣΠΣΠ(2) circuits, i.e., multilinear depth-4 circuits with fan-in 2 at the top + gate. The algorithm is given blackbox access to a polynomial f ∈ F[x1, . . . , xn] computable by a multilinear ΣΠΣΠ(2) circuit of size s and outputs an equivalent multilinear ΣΠΣΠ(2) circuit, runs in time poly(n, s), and works over any field F. This is the first reconstruction result for any model of depth-4 arithmetic circuits. Prior to our work, reconstruction resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…makes sense to talk about a depth reduction for ΣΠΣΠ circuits as well.) ΣΠΣΠ(r) circuits have received significant attention for the problems of polynomial identity testing and polynomial reconstruction [KMSV10,SV11,GKL12], however prior to this work there were no nontrivial lower bounds for this class of circuits for any value of r ≥ 2.…”
Section: Our Resultsmentioning
confidence: 99%
“…makes sense to talk about a depth reduction for ΣΠΣΠ circuits as well.) ΣΠΣΠ(r) circuits have received significant attention for the problems of polynomial identity testing and polynomial reconstruction [KMSV10,SV11,GKL12], however prior to this work there were no nontrivial lower bounds for this class of circuits for any value of r ≥ 2.…”
Section: Our Resultsmentioning
confidence: 99%
“…Very recently Gupta, Kayal and Lokam [20] have used theorem 7 to solve worst-case reconstruction problem for depth-4 multilinear circuits of top fanin two. In a separate work, the authors have also found theorem 4 useful towards a certain version of the reconstruction problem for algebraic branching programs (ABPs).…”
Section: Discussionmentioning
confidence: 99%
“…. , w d−1 ), and assume 18 that w k > 1 for every k ∈ [d − 1]. Then the output of the algorithm is a full rank ABP of width w or (w d−1 , w d−2 , .…”
Section: Definition 4 (Full Rank Algebraic Branching Program)mentioning
confidence: 99%
“…As the linear form pq , it must be that Z ∈ Z w k . Moreover, any Z ∈ Z w k can be used along with the relations Q k+1 = Z • Q k+1 and Q k = −Q k • Z to satisfy Equation (18) and hence also Equations (16) and (17).…”
Section: Lemma 33 (Restated) the Space Wmentioning
confidence: 99%